Substantiation of the effectiveness of the use of interactive learning tools at the stage of initial training in sports games - Maksimenko, I. G.; Maksimenko, G. N.; Spirin, M. P.; Konovalov, V. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to substantiate rational schemes for the use of interactive teaching aids at the stage of initial training of athletes using the example of football.